Carbon nanotube grafted ABS modified nylon 6 composite material and preparation method thereof

By grafting ABS modified nylon 6 composite material, carbon nanotubes and ABS are used to graft the graft reaction and melt blend with nylon 6, the problem of poor mechanical properties of nylon 6 is solved and its toughness is significantly improved and impact resistance.

CN119410139AActive Publication Date: 2025-02-11ANHUI YUHUA TEXTILE

Patent Information

Application Number
CN202411816477.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-11
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

Due to its poor mechanical properties and insufficient impact resistance, Nylon 6 material has limited its application in automobiles, electronics and medical devices.

Method used

By grafting ABS modified nylon 6 composite material, carbon nanotubes and ABS are grafted to form carbon nanotubes grafted ABS, and then melt blended with nylon 6 to form composite material.

Benefits of technology

This method effectively improves the toughness and impact resistance of nylon 6, avoids the problems of uneven agglomeration and dispersion of carbon nanotubes, and forms a uniform network structure to absorb external forces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410139A_ABST
    Figure CN119410139A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nylon 6, and discloses a carbon nanotube grafted ABS modified nylon 6 composite material, acylating chlorinated carbon nanotubes and lysine are subjected to an amidation reaction, double bonds on ABS and double bonds on maleic anhydride are combined, anhydride modified ABS and amino modified carbon nanotubes are subjected to a ring-opening reaction, and the carbon nanotube grafted ABS modified nylon 6 composite material is obtained. The carbon nanotubes are grafted to the ABS, agglomeration of the carbon nanotubes is avoided, the carbon nanotubes can form a uniform network structure under the action of external force, a large amount of external force is absorbed, the toughness of a matrix is improved, a large amount of carboxyl introduced to the surface of the ABS plastic and amide groups in the nylon 6 matrix are subjected to hydrogen-bond interaction, a three-dimensional hydrogen-bond network is formed, and the toughness of the matrix is improved. According to the present invention, the compatibility and the interfacial force between the nylon 6 and the carbon nano-tube grafted ABS are improved, such that the nylon 6 and the carbon nano-tube grafted ABS can be uniformly distributed so as to form the sea island structure, and can buffer more stress effects under the action of the external force, such that the obtained composite material has excellent toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nylon 6, in particular to a carbon nanotube-grafted ABS modified nylon 6 composite material and a preparation method thereof. Background Art

[0002] Nylon 6 has good mechanical properties, corrosion resistance, corrosion resistance and processability. It is a material widely used in the fields of automobiles, electronic appliances and medical equipment. However, due to its good water absorption, poor stability, poor toughness and poor impact resistance, the application scope of nylon 6 is largely limited. Modifying nylon by polymer alloy method and adding polymer materials such as elastomer rubber to nylon 6 can effectively improve the notch impact strength of the matrix and achieve toughening effect. By adding nano-sized inorganic nanomaterials, when the nylon 6 matrix is ​​subjected to external force, it can also absorb the external force to a large extent, effectively improving the toughness of the nylon 6 matrix.

[0003] Carbon nanotubes are cheap and widely available. They are an inorganic nanomaterial with excellent mechanical properties. Chinese patent CN106046765B provides a method for preparing reinforced and toughened nylon 6 resin and nylon alloy. Liquid rubber and carbon nanotubes are grafted and anionic polymerization is used to prepare carbon nanotube-doped rubber-modified nylon 6 resin, which effectively improves the uneven dispersion of carbon nanotubes, but has a poor effect on improving the toughness of the nylon 6 matrix. By using modified ABS and carbon nanotubes to modify the nylon 6 model, the toughness of the obtained composite material is greatly improved, and it has excellent impact strength. Summary of the invention

[0004] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a carbon nanotube-grafted ABS modified nylon 6 composite material and a preparation method thereof, which solves the problem of poor mechanical properties of nylon 6.

[0005] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: a carbon nanotube grafted ABS modified nylon 6 composite material, the carbon nanotube grafted ABS modified nylon 6 composite material and the preparation method are as follows: (1) After uniformly dispersing N,N-dimethylformamide solvent, carboxylated carbon nanotubes and thionyl chloride by ultrasonication, heating and refluxing, reacting at 110-150°C for 24-36 hours, and obtaining acyl chloride carbon nanotubes after the reaction is completed; (2) stirring and mixing N,N-dimethylformamide solvent, acyl chloride carbon nanotubes and lysine to uniformly react, and after the reaction is completed, amino-modified carbon nanotubes are obtained; (3) After ABS (acrylonitrile-butadiene-styrene copolymer), maleic anhydride and dicumyl peroxide are stirred and mixed evenly, the mixture is transferred to a twin-screw extruder and reacted at 180-200°C for 8-15 minutes. After the reaction is completed, the mixture is extruded and granulated to obtain anhydride-modified ABS; (4) stirring and mixing the acetone solvent, the anhydride-modified ABS and the amino-modified carbon nanotubes, heating and refluxing, and reacting at 70-90° C. for 6-12 hours. After the reaction is completed, carbon nanotube-grafted ABS is obtained; (5) After nylon 6, carbon nanotube grafted ABS and defoaming agent polydimethylsiloxane are mixed evenly, they are transferred to a twin-screw extruder, melt-blended at 210-230° C. for 6-12 min, with a screw speed of 300-400 r / min, and extruded to obtain a carbon nanotube grafted ABS modified nylon 6 composite material.

[0006] Preferably, in step (1), the mass ratio of N,N-dimethylformamide, carboxylated carbon nanotubes and thionyl chloride is 1500-3000:100:2500-5000.

[0007] Preferably, in step (2), the mass ratio of N,N-dimethylformamide, chlorinated carbon nanotubes and lysine is 4000-7000:100:55-85.

[0008] Preferably, the reaction temperature in step (2) is 80-100° C., and the reaction time is 18-24 h.

[0009] Preferably, in step (3), the mass ratio of ABS, maleic anhydride and dicumyl peroxide is 100:12-25:0.2-0.6.

[0010] Preferably, in step (4), the mass ratio of acetone, anhydride-modified ABS and amino-modified carbon nanotubes is 1200-3500:100:10-30.

[0011] Preferably, in step (5), the mass ratio of nylon 6, carbon nanotube grafted ABS and defoaming agent polydimethylsiloxane is 100:5-25:0.5-2.

[0012] 3. Beneficial technical effects Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a carbon nanotube grafted ABS modified nylon 6 composite material. In an N,N-dimethylformamide solvent, an acyl chloride group on an acyl chloride carbon nanotube and an amino terminal on lysine undergo an amidation reaction to obtain an amino-modified carbon nanotube. A double bond on the ABS generates a free radical under the action of an initiator, dicumyl peroxide, by a melt grafting method, and the free radical is combined with a double bond on maleic anhydride to obtain anhydride-modified ABS. In an acetone solvent, an acid anhydride on the anhydride-modified ABS and an amino group at the carboxyl terminal of the amino-modified carbon nanotube undergo a ring-opening reaction to obtain carbon nanotube grafted ABS. The carbon nanotube grafted ABS is added to a nylon 6 matrix and mixed to obtain a carbon nanotube grafted ABS modified nylon 6 composite material.

[0013] The carbon nanotube grafted ABS modified nylon 6 composite material has carbon nanotubes grafted onto ABS, which effectively avoids the agglomeration of carbon nanotubes and solves the problem of uneven dispersion of inorganic nanomaterials during the blending process. When subjected to external force, the carbon nanotubes can form a uniform network structure, absorb a large amount of external force, and improve the toughness of the matrix. The ABS plastic has the characteristics of good stability and excellent mechanical properties. A large number of carboxyl groups introduced on the surface and carboxyl groups obtained by ring-opening of anhydride can both hydrogen bond with amide groups in the nylon 6 matrix to form a three-dimensional hydrogen bond network, effectively improving the compatibility and interface force between nylon 6 and carbon nanotube grafted ABS, so that they can be more evenly distributed to form an island structure. When subjected to external force, more stress can be buffered, and the obtained composite material has excellent toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the structure of amino-modified carbon nanotubes. DETAILED DESCRIPTION

[0015] To achieve the above object, the present invention provides the following specific implementation methods and examples: A method for preparing a carbon nanotube-grafted ABS-modified nylon 6 composite material is as follows: (1) Add N,N-dimethylformamide solvent, carboxylated carbon nanotubes and thionyl chloride in a mass ratio of 1500-3000:100:2500-5000 to a reaction bottle, disperse them uniformly by ultrasonication, heat and reflux, react at 110-150°C for 24-36 hours, and after the reaction is completed, rotary evaporate, wash with tetrahydrofuran, and dry to obtain acyl chloride carbon nanotubes; (2) Add N,N-dimethylformamide solvent, chlorinated carbon nanotubes and lysine in a mass ratio of 4000-7000:100:55-85 to the reaction bottle, stir and mix evenly, react at 80-100°C for 18-24h, and after the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified carbon nanotubes; (3) ABS, maleic anhydride and dicumyl peroxide in a mass ratio of 100:12-25:0.2-0.6 are added to the reaction bottle in sequence, and after being stirred and mixed evenly, the mixture is transferred to a twin-screw extruder and reacted at 180-200°C for 8-15 minutes. After the reaction is completed, the mixture is extruded and granulated, washed with acetone, precipitated with ethanol, filtered and dried to obtain anhydride-modified ABS; (4) Add acetone solvent, anhydride-modified ABS and amino-modified carbon nanotubes in a mass ratio of 1200-3500:100:10-30 to the reaction bottle in sequence, stir and mix evenly, heat and reflux, and react at 70-90°C for 6-12 hours. After the reaction is completed, cool, filter, wash with methanol, and dry to obtain carbon nanotube-grafted ABS; (5) Add nylon 6, carbon nanotube grafted ABS and defoaming agent polydimethylsiloxane in a mass ratio of 100:5-25:0.5-2 into a high-speed mixer in sequence, mix well, transfer to a twin-screw extruder, melt blend at 210-230°C for 6-12 minutes, and extrude at a screw speed of 300-400 r / min to obtain a carbon nanotube grafted ABS modified nylon 6 composite material. Example 1

[0016] (1) 150 g of N,N-dimethylformamide solvent, 10 g of carboxylated carbon nanotubes and 250 g of thionyl chloride were added to a reaction bottle in sequence, and after being uniformly dispersed by ultrasonication, the mixture was heated under reflux and reacted at 110°C for 24 h. After the reaction was completed, the mixture was rotary evaporated, washed with tetrahydrofuran and dried to obtain acyl chloride carbon nanotubes; (2) Add 400 g of N,N-dimethylformamide solvent, 10 g of acyl chloride carbon nanotubes and 5.5 g of lysine to the reaction bottle in sequence, stir and mix evenly, react at 80°C for 18 h, and after the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified carbon nanotubes; (3) 100 g of ABS, 12 g of maleic anhydride and 0.2 g of diisopropylbenzene peroxide were added to the reaction bottle in sequence, and after being stirred and mixed evenly, the mixture was transferred to a twin-screw extruder and reacted at 180 °C for 8 min. After the reaction was completed, the mixture was extruded and granulated, washed with acetone, precipitated with ethanol, filtered and dried to obtain anhydride-modified ABS; (4) Add 120 g of acetone solvent, 10 g of anhydride-modified ABS and 1 g of amino-modified carbon nanotubes to the reaction bottle in sequence, stir and mix evenly, heat and reflux, and react at 70 ° C for 6 h. After the reaction is completed, cool, filter, wash with methanol, and dry to obtain carbon nanotube-grafted ABS; (5) 50 g of nylon 6, 2.5 g of carbon nanotube-grafted ABS and 0.25 g of defoaming agent polydimethylsiloxane were added to a high-speed mixer in sequence. After mixing evenly, the mixture was transferred to a twin-screw extruder and melt-blended at 210 °C for 6 min at a screw speed of 300 r / min. The mixture was extruded to obtain a carbon nanotube-grafted ABS modified nylon 6 composite material. Example 2

[0017] (1) 180 g of N,N-dimethylformamide solvent, 10 g of carboxylated carbon nanotubes and 320 g of thionyl chloride were added to a reaction bottle in sequence, and after being uniformly dispersed by ultrasonication, the mixture was heated to reflux and reacted at 120°C for 28 h. After the reaction was completed, the mixture was rotary evaporated, washed with tetrahydrofuran, and dried to obtain chlorinated carbon nanotubes; (2) Add 480 g of N,N-dimethylformamide solvent, 10 g of acyl chloride carbon nanotubes and 6.4 g of lysine to the reaction bottle in sequence, stir and mix evenly, react at 85°C for 20 h, and after the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified carbon nanotubes; (3) 100 g of ABS, 15 g of maleic anhydride and 0.3 g of diisopropylbenzene peroxide were added to the reaction bottle in sequence, and after being stirred and mixed evenly, the mixture was transferred to a twin-screw extruder and reacted at 185 °C for 9 min. After the reaction was completed, the mixture was extruded and granulated, washed with acetone, precipitated with ethanol, filtered and dried to obtain anhydride-modified ABS; (4) Add 180 g of acetone solvent, 10 g of anhydride-modified ABS and 1.5 g of amino-modified carbon nanotubes to the reaction bottle in sequence, stir and mix evenly, heat and reflux, and react at 75 ° C for 8 h. After the reaction is completed, cool, filter, wash with methanol, and dry to obtain carbon nanotube-grafted ABS; (5) 50 g of nylon 6, 5 g of carbon nanotube-grafted ABS and 0.4 g of defoaming agent polydimethylsiloxane were added to a high-speed mixer in sequence. After mixing evenly, the mixture was transferred to a twin-screw extruder and melt-blended at 215 °C for 8 min at a screw speed of 320 r / min. The mixture was extruded to obtain a carbon nanotube-grafted ABS modified nylon 6 composite material. Example 3

[0018] (1) Add 240 g of N,N-dimethylformamide solvent, 10 g of carboxylated carbon nanotubes and 380 g of thionyl chloride to a reaction bottle in sequence, disperse them uniformly by ultrasonication, heat and reflux, and react at 130°C for 30 h. After the reaction is completed, evaporate the mixture, wash with tetrahydrofuran, and dry to obtain chlorinated carbon nanotubes; (2) Add 550 g of N,N-dimethylformamide solvent, 10 g of acyl chloride carbon nanotubes and 7.2 g of lysine to the reaction bottle in sequence, stir and mix evenly, react at 90°C for 21 h, and after the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified carbon nanotubes; (3) 100 g of ABS, 18 g of maleic anhydride and 0.4 g of diisopropylbenzene peroxide were added to the reaction bottle in sequence, and after being stirred and mixed evenly, the mixture was transferred to a twin-screw extruder and reacted at 190 °C for 10 min. After the reaction was completed, the mixture was extruded and granulated, washed with acetone, precipitated with ethanol, filtered and dried to obtain anhydride-modified ABS; (4) Add 250 g of acetone solvent, 10 g of anhydride-modified ABS and 2 g of amino-modified carbon nanotubes to the reaction bottle in sequence, stir and mix evenly, heat and reflux, and react at 80°C for 9 h. After the reaction is completed, cool, filter, wash with methanol, and dry to obtain carbon nanotube-grafted ABS; (5) 50 g of nylon 6, 7.5 g of carbon nanotube-grafted ABS and 0.6 g of defoaming agent polydimethylsiloxane were added to a high-speed mixer in sequence. After mixing evenly, the mixture was transferred to a twin-screw extruder and melt-blended at 220 °C for 9 min at a screw speed of 350 r / min. The mixture was extruded to obtain a carbon nanotube-grafted ABS modified nylon 6 composite material. Example 4

[0019] (1) Add 280 g of N,N-dimethylformamide solvent, 10 g of carboxylated carbon nanotubes and 450 g of thionyl chloride to a reaction bottle in sequence, disperse them uniformly by ultrasonication, heat under reflux, and react at 140°C for 32 hours. After the reaction is completed, evaporate the mixture, wash with tetrahydrofuran, and dry to obtain chlorinated carbon nanotubes; (2) Add 640 g of N,N-dimethylformamide solvent, 10 g of acyl chloride carbon nanotubes and 8 g of lysine to the reaction bottle in sequence, stir and mix evenly, react at 95 °C for 22 h, and after the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified carbon nanotubes; (3) 100 g of ABS, 22 g of maleic anhydride and 0.5 g of diisopropylbenzene peroxide were added to the reaction bottle in sequence, and after being stirred and mixed evenly, the mixture was transferred to a twin-screw extruder and reacted at 195 °C for 12 min. After the reaction was completed, the mixture was extruded into granules, washed with acetone, precipitated with ethanol, filtered and dried to obtain anhydride-modified ABS; (4) Add 300 g of acetone solvent, 10 g of anhydride-modified ABS and 2.5 g of amino-modified carbon nanotubes to the reaction bottle in sequence, stir and mix evenly, heat to reflux, and react at 85°C for 10 h. After the reaction is completed, cool, filter, wash with methanol, and dry to obtain carbon nanotube-grafted ABS; (5) 50 g of nylon 6, 10 g of carbon nanotube-grafted ABS and 0.8 g of defoaming agent polydimethylsiloxane were added to a high-speed mixer in sequence. After mixing evenly, the mixture was transferred to a twin-screw extruder and melt-blended at 225 °C for 10 min at a screw speed of 380 r / min. The mixture was extruded to obtain a carbon nanotube-grafted ABS modified nylon 6 composite material. Example 5

[0020] (1) Add 300 g of N,N-dimethylformamide solvent, 10 g of carboxylated carbon nanotubes and 500 g of thionyl chloride to a reaction bottle in sequence, disperse evenly by ultrasonication, heat under reflux, and react at 150 °C for 36 h. After the reaction is completed, perform rotary evaporation, wash with tetrahydrofuran, and dry to obtain chlorinated carbon nanotubes; (2) Add 700 g of N,N-dimethylformamide solvent, 10 g of acyl chloride carbon nanotubes and 8.5 g of lysine to the reaction bottle in sequence, stir and mix evenly, react at 100 ° C for 24 hours, and after the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified carbon nanotubes; (3) 100 g of ABS, 25 g of maleic anhydride and 0.6 g of diisopropylbenzene peroxide were added to the reaction bottle in sequence, and after being stirred and mixed evenly, the mixture was transferred to a twin-screw extruder and reacted at 200 °C for 15 min. After the reaction was completed, the mixture was extruded and granulated, washed with acetone, precipitated with ethanol, filtered and dried to obtain anhydride-modified ABS; (4) Add 350 g of acetone solvent, 10 g of anhydride-modified ABS and 3 g of amino-modified carbon nanotubes to the reaction bottle in sequence, stir and mix evenly, heat and reflux, and react at 90°C for 12 h. After the reaction is completed, cool, filter, wash with methanol, and dry to obtain carbon nanotube-grafted ABS; (5) 50 g of nylon 6, 12.5 g of carbon nanotube-grafted ABS and 1 g of defoaming agent polydimethylsiloxane were added to a high-speed mixer in sequence. After mixing evenly, the mixture was transferred to a twin-screw extruder and melt-blended at 230 °C for 12 min at a screw speed of 400 r / min. The mixture was extruded to obtain a carbon nanotube-grafted ABS modified nylon 6 composite material.

[0021] Comparative Example 1 (1) Add 250 g of N,N-dimethylformamide solvent, 10 g of carboxylated carbon nanotubes and 400 g of thionyl chloride to a reaction bottle in sequence, disperse them uniformly by ultrasonication, heat under reflux, and react at 130°C for 32 hours. After the reaction is completed, evaporate the mixture, wash with tetrahydrofuran, and dry to obtain chlorinated carbon nanotubes; (2) Add 550 g of N,N-dimethylformamide solvent, 10 g of acyl chloride carbon nanotubes and 7 g of lysine to the reaction bottle in sequence, stir and mix evenly, react at 90°C for 22 h, and after the reaction is completed, wash with deionized water and ethanol, and dry to obtain amino-modified carbon nanotubes; (3) 50 g of nylon 6, 7.5 g of carbon nanotube-grafted ABS and 0.4 g of defoaming agent polydimethylsiloxane were added to a high-speed mixer in sequence. After mixing evenly, the mixture was transferred to a twin-screw extruder and melt-blended at 220 °C for 9 min. The screw speed was 350 r / min and the mixture was extruded to obtain a carbon nanotube-modified nylon 6 composite material.

[0022] The prepared nylon 6 composite material was subjected to an impact strength test on an XCJ25 simply supported beam impact testing machine, and the national standard for the test was GB / T 1843-2008.

[0023]

[0024] The prepared nylon 6 composite material was subjected to a flexural strength test on a CTM8000 flexural strength testing machine, and the national standard for the test was GB / T 1402-79.

[0025]

Claims

1. A method for preparing a carbon nanotube-grafted ABS modified nylon 6 composite material, characterized in that: The preparation method is as follows: (1) After uniformly dispersing N,N-dimethylformamide solvent, carboxylated carbon nanotubes and thionyl chloride by ultrasonication, heating and refluxing, reacting at 110-150°C for 24-36 hours, and obtaining acyl chloride carbon nanotubes after the reaction is completed; (2) stirring and mixing N,N-dimethylformamide solvent, acyl chloride carbon nanotubes and lysine to uniformly react, and after the reaction is completed, amino-modified carbon nanotubes are obtained; (3) After ABS (acrylonitrile-butadiene-styrene copolymer), maleic anhydride and dicumyl peroxide are stirred and mixed evenly, the mixture is transferred to a twin-screw extruder and reacted at 180-200°C for 8-15 minutes. After the reaction is completed, the mixture is extruded and granulated to obtain anhydride-modified ABS; (4) stirring and mixing the acetone solvent, the anhydride-modified ABS and the amino-modified carbon nanotubes, heating and refluxing, and reacting at 70-90° C. for 6-12 hours. After the reaction is completed, carbon nanotube-grafted ABS is obtained; (5) After nylon 6, carbon nanotube grafted ABS and defoaming agent polydimethylsiloxane are mixed evenly, they are transferred to a twin-screw extruder, melt-blended at 210-230° C. for 6-12 min, with a screw speed of 300-400 r / min, and extruded to obtain a carbon nanotube grafted ABS modified nylon 6 composite material.

2. The method for preparing a carbon nanotube-grafted ABS modified nylon 6 composite material according to claim 1, characterized in that: In the step (1), the mass ratio of N,N-dimethylformamide, carboxylated carbon nanotubes and thionyl chloride is 1500-3000:100:2500-5000.

3. The method for preparing a carbon nanotube-grafted ABS modified nylon 6 composite material according to claim 1, characterized in that: In the step (2), the mass ratio of N,N-dimethylformamide, chlorinated carbon nanotubes and lysine is 4000-7000:100:55-85.

4. The method for preparing a carbon nanotube-grafted ABS modified nylon 6 composite material according to claim 1, characterized in that: The reaction temperature in step (2) is 80-100° C. and the reaction time is 18-24 hours.

5. The method for preparing a carbon nanotube-grafted ABS modified nylon 6 composite material according to claim 1, characterized in that: In the step (3), the mass ratio of ABS, maleic anhydride and dicumyl peroxide is 100:12-25:0.2-0.

6.

6. The method for preparing a carbon nanotube-grafted ABS modified nylon 6 composite material according to claim 1, characterized in that: In the step (4), the mass ratio of acetone, anhydride-modified ABS and amino-modified carbon nanotubes is 1200-3500:100:10-30.

7. The method for preparing a carbon nanotube-grafted ABS modified nylon 6 composite material according to claim 1, characterized in that: In the step (5), the mass ratio of nylon 6, carbon nanotube grafted ABS and defoaming agent polydimethylsiloxane is 100:5-25:0.5-2.

Citation Information

Patent Citations

  • Reinforced and Toughened Nylon 6 Resin, Nylon Alloy and Preparation Method

    CN106046765B

  • Preparation method and application of carbon nanotube modified nylon 66 flame-retardant composite material

    CN115505229A

  • Highly water-soluble carbon nanometer tube preparation method

    CN1733602A

  • Complex containing nylon and carbon nanotubes and manufacturing method thereof

    KR1020140062580A

Cited By

  • Carbon nanotube-based PPE material and preparation method thereof

    CN119708814A

  • Velvet polishing brush wire and preparation method thereof

    CN120590792A

  • A type of open-pile polishing brush bristles and its preparation method

    CN120590792B

  • High-heat-resistance and high-toughness PA11T composite material and preparation method thereof

    CN121991503A